Teaching self-efficacy in inclusive education and characteristics of the teaching context - Nina, Karla (2022)
The objective of this study was to describe the association of teachers' self-efficacy in inclusive educational practices with variables of the teaching context and teachers' characteristics. There were 193 teachers in basic education, 77.72 % female and 22.28 % male from private, confessional and public state schools located in the municipalities of Belém and Castanhal, Pará, Brazil. The instruments of characterization and the scale of effectiveness of teachers in inclusive educational practices were applied. The data analysis techniques were factorial analysis and correspondence analysis. Among the results found, associations between the investigated variables were verified, which suggests that when judging one's own capacity in inclusive educational practices, the teacher considers some factors present in the context and in his or her teaching path. It is hoped that this study can contribute to the stimulation of continued teacher education in the inclusive context.